Efficacy of gabapentin for the prevention of postherpetic neuralgia in patients with acute herpes zoster: A double blind, randomized controlled trial - Bulilete, Oana (PLoS One, 2019)
BACKGROUND: Postherpetic neuralgia (PHN) is the most common complication of herpes zoster (HZ). Previous trials have reported that gabapentin can relieve chronic neuropathic pain, but its effect on prevention of PHN is unclear. OBJECTIVE: To assess the efficacy of a 5-week course of gabapentin on acute herpetic pain and on the prevention of PHN at 12 weeks in patients with acute HZ. METHODS: This was a randomized, double blind, placebo-controlled trial conducted in 17 primary care health centers in Mallorca, Spain. All patients were older than 50 years, presented with HZ within 72 h of rash onset, and had moderate-severe pain (≥4 on a 10-point visual analogue scale [VAS]). Ninety-eight patients were randomized to receive gabapentin or placebo. All patients received valaciclovir for 7 days and analgesia if needed. The treatment period was 5 weeks, followed by 7 weeks of follow-up. Gabapentin was initiated at 300 mg/day and gradually titrated to a maximum of 1800 mg/day. The main outcome measure was pain at 12 weeks. RESULTS: Seventy-five patients completed the study, 33 in the gabapentin group and 42 in the control group. A total of 18.2% of patients in the gabapentin group and 9.5% in the control group reported pain at 12 weeks (p = 0.144). Four patients in the gabapentin group (12.1%), but no patients in the placebo group, reported pain of 4 or more on a 10-point VAS. Patients taking gabapentin reported worse health-related quality of life and poorer sleep quality. Three patients discontinued the trial due to adverse effects from gabapentin. CONCLUSION: Addition of gabapentin to the usual treatment of HZ within 72 h of rash onset provided no significant relief from acute herpetic pain or prevention of PHN. TRIAL REGISTRATION: ISRCTN Registry identifier: ISRCTN79871784